1977
DOI: 10.4319/lo.1977.22.5.0846
|View full text |Cite
|
Sign up to set email alerts
|

Biological transport of zinc‐65 into the deep sea1

Abstract: The specific activities of zinc-65 ('"Zn : Zn) in pelagic and benthic animals collected off Oregon were correlated with depth of capture to estimate vertical biological transport rates. Results suggest that about 2 yr are required for transport of aZn from near-surface to abyssobenthic animals. Vertical transport appears to be slower in upper waters, suggesting recycling of zinc within biological communities, and more rapid below 500 m. The long vertical transport time for zinc contrasts with the shorter times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Pearlside was not a major constituent in the deepest tow. Lantern fish and pearlside perform daily vertical migrations that can span 100 s of meters [28] [27] , while blue whiting, the largest and fastest swimmer, normally occupy deep water (300–500 m) with limited vertical movements [29] . In the Iceland Basin we evaluated the species composition at a station in the last eddy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pearlside was not a major constituent in the deepest tow. Lantern fish and pearlside perform daily vertical migrations that can span 100 s of meters [28] [27] , while blue whiting, the largest and fastest swimmer, normally occupy deep water (300–500 m) with limited vertical movements [29] . In the Iceland Basin we evaluated the species composition at a station in the last eddy.…”
Section: Resultsmentioning
confidence: 99%
“…Similar behaviour by fish feeding on plankton will amplify observed patterns of acoustically-detectable biomass. In addition to extensive diel migrations as seen in the upper part of the water column, lantern fish also exhibit a lethargic behaviour [28] where they can be passively displaced by changes in water mass density or currents [43] . The combination of swimming and passive transport caused by eddy dynamics, enables mesopelagic fish to track concentrations of zooplankton prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deeper in the water column, the acoustic record revealed that the layer of mesopelagic fish was displaced by several hundred meters downwards at the center of the eddy compared to the region outside the eddy (Godø et al, 2012). Some mesopelagic fish exhibit lethargic behavior, probably as a strategy to conserve energy in an environment where food is relatively scarce (Pearcy et al, 1977;Luck and Pietsch, 2008) and may thus also be subject to the hydrodynamic conditions that act in the eddy.…”
Section: Introductionmentioning
confidence: 99%